2015
DOI: 10.1007/s13197-015-2143-2
|View full text |Cite
|
Sign up to set email alerts
|

Red fresh vegetables smoothies with extended shelf life as an innovative source of health-promoting compounds

Abstract: Two fresh red vegetables smoothies based on tomato, carrots, pepper and broccoli and rich in healthpromoting compounds were developed. The smoothies showed a viscoelastic behaviour. According to sensory analyses, a shelf life of 28 days at 5°C for fresh blended smoothies was established while thermally-treated ones (3 min, 80°C) reached up to 40 days at 20°C and 58 days at 5°C. For those mild heat treated smoothies, total vitamin C degradation was 2-fold reduced during storage at 5°C compared to samples stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
3
6

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 28 publications
1
58
3
6
Order By: Relevance
“…Rheological measurements were executed using an ARG2 stress-controlled rheometer (TA Instruments, New Castle, DE, USA) equipped with serrated (to prevent wall depletion phenomena) plate-plate geometry (20 mm, gap 2 mm) according to Castillejo et al (2016). Briefly, oscillatory tests were performed within the linear viscoelastic region for the samples previously equilibrated (25 C for 1 min) between the plates.…”
Section: Rheological Properties Of Smoothiesmentioning
confidence: 99%
“…Rheological measurements were executed using an ARG2 stress-controlled rheometer (TA Instruments, New Castle, DE, USA) equipped with serrated (to prevent wall depletion phenomena) plate-plate geometry (20 mm, gap 2 mm) according to Castillejo et al (2016). Briefly, oscillatory tests were performed within the linear viscoelastic region for the samples previously equilibrated (25 C for 1 min) between the plates.…”
Section: Rheological Properties Of Smoothiesmentioning
confidence: 99%
“…Accordingly, whitening index (WI) and browning index (BI) were calculated from CIE Lab parameters according to Eqs. (3) and (4) as previously described (Castillejo et al 2015;Martínez-Hernández et al 2016;Palou et al 1999).…”
Section: Colormentioning
confidence: 99%
“…These findings indicate that smoothies have a potential role to play in narrowing gaps where dietary fibre and micronutrient shortfalls exist. For example, in one study red vegetable smoothie consumption provided a substantial proportion of the recommended daily nutrient intake for dietary fibre, minerals and vitamin C across different population groups [13].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of in Utah providing fruit smoothies during school breakfast amongst middle school and high school children found that the proportion of students eating a full serving of whole fruit increased from 4.3% to 45.1% over a 10-week period [12]. Other work found that consuming a 250 ml portion of a red smoothie containing tomato, carrots, pepper and broccoli played a key role in contributing to recommended daily nutrient intakes for dietary fibre, minerals and vitamin C of different population groups [13].…”
Section: Researchmentioning
confidence: 99%